Studies in historical improvisation: from Cantare super librum do Partimenti, ed. Massimiliano Guido, Abingdon, New York 2017 - Wysocki, Michał (Muzyka, 2018)
Recenzja książki: "Studies in historical improvisation: from Cantare super librum do Partimenti", red. Massimiliano Guido, Abingdon, New York 2017